Contextual variables affect peak running performance in elite soccer players: A brief report - Augusto, Diêgo; Brito, João; Aquino, Rodrigo; Paulucio, Dailson; Figueiredo, Pedro; Bedo, Bruno Luiz Souza; Touguinhó, Deborah; Vasconcellos, Fabrício (Frontiers in Sports and Active Living, 2022)
The current brief research report aimed to investigate the influence of contextual variables on peak running performance in male elite soccer players. We analyzed 29 matches of an elite soccer team during the Brazilian Serie A 2019. Twenty players were tracked using GPS units. Peak physical performance was determined using moving average running values with different time windows (1, 3, and 5-min periods). The variables analyzed were total distance covered, total distance covered in high-intensity running (≥19.8 km·h−1), and the distance in accelerations (≥2 m·s−2) and decelerations ( ≤-2 m·s−2). Four contextual variables were considered: 1) positional status; 2) match location; 3) match outcome; and 4) match status. Central defenders showed a lower 1-min peak total distance in relation to all other positions (p = 0.001–0.03). Peak physical performance was higher in away matches for high-intensity running, acceleration, and deceleration (p = 0.01–0.03). In matches that ended in losses, peak values for high-intensity running and acceleration were higher compared to draws and wins (p = 0.01–0.04). Regarding the match status, higher values were observed in draws than wins and losses (p = 0.01). Peak running performance vary according to contextual variables of the match in male elite soccer players. Positional differences were found for peak periods, and physical performance was higher in away matches.